Gaucher's disease and retinitis pigmentosa : A case report - Nadir KAYA,; Mustafa KETENCİ,; Arif KOŞAR,; Nurşen ARITÜRK,; İlkser AKPOLAT,; Levent ALTINTOP,; Hakkı KAHRAMAN, (Turkish Journal of Gastroenterology, 2019)
-